An overview of Treatment options for urinary stones - Hamid Shafi; Bobak Moazzami; Mohsen Pourghasem (Caspian Journal of Internal Medicine, 2016)
Urolithiasis has become a worldwide problem with the prevalence of the disease increasing over the past few decades. While various treatment modalities have evolved over the years, discrepancies exist regarding the clinical indications and the efficacy of each of these treatment options. In the present review, we aim to review the current treatment modalities for urinary tract stones to provide a better understanding on the therapeutic approaches as well as their clinical indications.